2021
DOI: 10.1002/cbin.11685
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐26a‐5p alleviates cardiac hypertrophy and dysfunction via targeting ADAM17

Abstract: Cardiac hypertrophy has been a high prevalence rate throughout the world. It has posed a big threat to public health due to limited therapeutic approaches. Previous studies showed that pathological cardiac hypertrophy was associated with autophagy, microRNAs (miRNA), and other signaling pathways, while the molecular mechanisms remain incompletely characterized. In this study, we used thoracic aortic constriction (TAC)‐induced mice and angiotensin‐II (Ang‐II)‐induced H9C2 cell line as cardiac hypertrophy model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…For example, Shi et al. found that miR-26a-5p alleviated cardiac hypertrophy and dysfunction by targeting ADAM17 [ 27 ]. In addition, miR-26a-5p has been reported to play crucial roles in multiple neoplastic diseases [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shi et al. found that miR-26a-5p alleviated cardiac hypertrophy and dysfunction by targeting ADAM17 [ 27 ]. In addition, miR-26a-5p has been reported to play crucial roles in multiple neoplastic diseases [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, delivery of miR-29a-3p has a beneficial effect in myocardial injury ( Ren et al, 2021 ) and cardiac hypertrophy ( Xie et al, 2020 ). Similarly, the hsa-mir-26a/b-5p was highly expressed in cardiac hypertrophy ( Tang et al, 2020 ) and promoted myocardial infarction-induced cell death ( Jung et al, 2021 ), yet overexpression of miR-26a/b attenuated cardiac fibrosis ( Tang et al, 2017 ; Wang et al, 2019 ) and alleviated cardiac hypertrophy and dysfunction ( Shi et al, 2021 ). Lastly, the hsa-mir-124-3p was reported to promote cardiac fibroblast activation and proliferation ( Zhu et al, 2021 ), and its inhibition protects against acute myocardial infarction by suppressing cardiomyocyte apoptosis ( Hu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also constructed a gene-miRNA regulatory network, and four miRNAs (mir-26a-5p, mir-1343-3p, mir-129-2-3p, and mir-124-3p) were identified because of their interaction at least with four hub DEARGs. Mir-26a-5p can alleviate cardiac hypertrophy and dysfunction ( Shi et al, 2021 ) and protect against myocardial ischemia/reperfusion injury ( Xing et al, 2020 ). Mir-1343-3p plays a significant role in the development of human cancers such as lung cancer ( Zhang et al, 2020 ), colorectal carcinoma ( Bhat et al, 2022 ), and hepatocellular carcinoma ( Mou and Sun, 2022 ).…”
Section: Discussionmentioning
confidence: 99%